Preliminary Study of an IPAS Learning Package Integrating Problem Based Learning, Deep Learning, and the Traditional Engklek Game for Elementary School Students - Entit Haryanti; Devi Apriyuni Yolanda; Yuyun Dwi Haryanti (FKIP - Universitas Riau, 2026)
IPAS (Integrated Natural and Social Sciences) learning in elementary schools plays an important role in developing students’ critical thinking skills. This preliminary study aimed to identify learning needs and formulate a conceptual design of an IPAS learning package integrating Problem-Based Learning (PBL), deep learning, and the traditional Engklek game. This study employed a qualitative descriptive approach involving 62 sixth-grade students and two teachers at SDN Karangsambung II. Data were collected through observations, interviews, and document analysis and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that IPAS learning remained predominantly teacher-centered, the implementation of PBL was not yet optimal, deep learning components had not been fully integrated into instructional materials and assessment practices, and traditional games had not been systematically utilized in learning activities. Based on the needs analysis and literature review, this study produced a conceptual design of a PBL-based IPAS learning package supported by the traditional Engklek game. The findings provide a foundation for further product development and validation to support more meaningful and contextual IPAS learning